Le zampe bugiarde del drago Tarantasio. Stratificazione di un immaginario mitografico tra estrattivismo energetico, iconografie aziendali e arte politica - Rossi, Marco (Antropologia Pubblica, 2024)
This paper explores the interplay of mythological imaginaries in Lodi’s territorial memories. It examines the myth of Lake Gerundo’s disappearance and dragon Tarantasio’s role, linking it to Eni’s post-war developments and highlighting debates in critical anthropology of heritage and ethnographic analyses of energy companies’ communication strategies. It also analyzes an artistic project which aims to manipulate this cultural heritage in order to promote awareness of political ecology practices. The work seeks to trace a cultural history of the relationships between inhabitants and their territory, emphasizing tensions surrounding the climate crisis and demonstrating how these can be addressed through artistic and cultural production. Tarantasio transitions from a local mythological entity to an emblem of extractive capitalism’s harmful impact. This transformation fosters both popular associations between Eni and Tarantasio and counter-hegemonic representations critiquing energy companies’ roles in the climate crisis. The paper underscores the convergence of energy companies, popular epistemologies and artistic endeavors in leveraging cultural heritage, understood as a source to be questioned and manipulated for respective rhetorical strategies.